Donation After Cardiac Death and the Emergency Department: Ethical Issues. (January 2014) - Simon, Jeremy R.; Schears, Raquel M.; Padela, Aasim I.; Goldstein, Joshua N.
Abstract Organ donation after cardiac death (DCD) is increasingly considered as an option to address the shortage of organs available for transplantation, both in the United States and worldwide. The procedures for DCD differ from procedures for donation after brain death and are likely less familiar to emergency physicians (EPs), even as this process is increasingly involving emergency departments (EDs). This article explores the ED operational and ethical issues surrounding this procedure.